(untitled) (Bangladesh Journal of Medical Science, 2025)
Background/Objectives Given that dental anxiety can significantly impact patient cooperation and treatment outcomes, it is crucial to implement effective strategies to alleviate this anxiety. This study aimed to evaluate the effect of VR as a distraction tool on pain and anxiety stages in pediatric patients who are undergoing routine dental treatments. Methods 60 pediatric patients aged 7 to 10 requiring pediatric dental therapy had been divided into two groups: an experimental group that applied virtual truth (VR) as a distraction device and a control group that obtained traditional care. Data on Anxiety and Pain tiers were collected using the Modified Child Dental Anxiety Scale (MCDAS) and the Wong-Baker Faces Pain Rating Scale earlier than and after the dental techniques. Statistical analyses have been accomplished to examine the effects among the two groups, focusing on differences in anxiety and pain levels. Results At baseline, Group A’s mean anxiety score was 4.12 ± 0.28; it reduced significantly to 1.89 ± 0.58 post-operatively, therefore displaying a 54% reduction. Pain levels were clearly improved as evaluations for the control group (Group B) fell from a baseline of 5.56 ± 0.48 to 1.10 ± 1.28 in Group A. The significantly significant (p < 0.001) differences in anxiety and pain measurements among the groups highlight how well Virtual Reality provides a diversion during dental treatment. Conclusions: The findings of this research show that using virtual reality as a distraction method helps children patients’ pain and anxiety levels to be considerably lowered during dental treatments. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 285-292